A scoping review of transmission models for soil-transmitted helminth infections to underpin the development of a transmission model for Strongyloides stercoralis - Mackrina Winslow; Juan Pablo Villanueva-Cabezas; Vito Colella; Patricia T. Campbell (Parasitology)
Soil-transmitted helminth (STH) infections afflict people worldwide, especially in tropical and subtropical regions. Strongyloides stercoralis is distinctive from other STH nematodes by its complex life cycle features of autoinfection, parthenogenesis, and environmental reproduction. This scoping review aims to identify the structures, features, and techniques employed in existing STH models, emphasizing their potential application in describing S. stercoralis infection dynamics. A comprehensive search was conducted in the Medline, Embase, and Scopus databases for studies published until 14 June 2024. A total of 47 studies presenting a new model or novel adaptation of an existing model to human STH infection transmission were identified: only one described S. stercoralis transmission in humans. The identified models were predominantly deterministic and focused on the dynamics of mean worm load within hosts and the infectiousness of the environmental reservoir. One model addressed transmission in multi-host scenarios, as not all STH transmission cycles involve multiple hosts. Models were frequently used to simulate the effectiveness of mass drug administration, including drug efficacy and treatment coverage, while water, sanitation, and hygiene (WASH), health education, and vaccination were less explored. Given the limitation of individual-level data, compartmental models may be a reasonable starting point for S. stercoralis transmission. For a comprehensive understanding, incorporating parasite life cycle features into the model, exploring multi-host dynamics, including a diverse range of host heterogeneities, and assessing the impact of climatic factors like rainfall and land surface temperature on parasite survival in the environment may be beneficial, especially in settings where their importance is notable.